The literature of silence at Ihab Hassan - Mohammed, Raniah Salam; Awada, Hanan Ali (Al-Adab Journal, 2021)
This research deals with the idea of silence literature according to Ihab Habib Hassan (1925-2015). Silence literature for him is a metaphor for an expression of a language that embodies the tensions of modern man. The literature of silence is not a harbinger of the death of the soul. Silence literature (a type of literature) is a concept he borrowed to explain modernity and postmodernity. Silence literature was part of the culture in the nineteenth century, and in the twentieth century it became an essential element in art visions. Hassan was interested in philosophy through the theory of knowledge, as silence does not mean the absence of meaning, but rather it is a positive phenomenon. Combining them generates a new type of new realistic belief.